Electrical conductivity of some points of acupuncture correlates with age, blood pressure and heart rate variability - Larysa I Khlopets'ka; Nataliya L Horkovenko; Walery Zukow (Kazimierz Wielki University, 2017)
Background. Thoughts about the informativeness of the parameters of acupuncture points are ambiguous, therefore studies in this direction remain relevant. Material and Methods. The object of observationwere 14 practically healthy men aged24-60years old. We recorded Blood Pressure ("Omron M4-I"), parameters of Heart Rate Variability ("CardioLab+HRV") and electroskin conductivity ("Medissa") in follow points of acupuncture: Pg(ND), TR(X) and MC(AVL) at Right and Left side, which represents,as it is believed, the nervous, endocrine and immune systems respectively. The survey was conductedtwo time with an interval of 4 days. Results processed by methods of correlation and canonical analyses, using the software package "Statistica 5.5". Results.The most informative among the registered parameters of the points of acupuncture are conductivity for TR(X) R&L as well as its Laterality Index for MC(AVL), which represent inversely Vagal tone and directly Sympathetic-Vagal balance, as well as Blood Pressure, to a greater extent Diastolic. Conclusion. Parameters of the points of acupuncture reflexes at least the state of the autonomic nervous system and associated blood pressure.